Drug Counselor Responses to Patients' Pain Reports: A Qualitative Investigation of Barriers and Facilitators to Treating Patients with Chronic Pain in Methadone Maintenance Treatment. Issue 11 (8th February 2017) - Beitel, Mark; Oberleitner, Lindsay; Kahn, Marissa; Kerns, Robert D.; Liong, Christopher; Madden, Lynn M.; Ginn, Joel; Barry, Declan T.
Abstract: Objective: To examine how drug counselors with no prior training in pain management respond to their patients' reports of chronic pain. Design, Setting, Subjects, and Methods: We conducted individual interviews with 30 drug counselors in methadone maintenance treatment. Interviews were audiotaped, transcribed, and systematically coded using the constant comparative method. Results: Participants identified counselor, patient, and logistical factors that serve as a barrier or facilitate their treatment of patients with chronic pain. Counselor barriers included lack of expertise in managing co-occurring chronic pain and opioid use disorder, complexity of patients' treatment needs, concerns about medication regimens, reliance on patient self-report, and absence of patient improvement. Counselor barriers facilitators included empathy, attending to small changes, and self-reflection. Counselors' perceptions of patient-related barriers included prior negative interactions with medical providers, diminished social roles, attenuated motivation, and negative attitudes toward opioid use disorder. Logistical barriers included lack of appropriate pain management referrals, limited counselor time, and attenuated treatment adherence; a logistical facilitator was consulting with medical providers. Conclusions: Perceived barriers to treating patients with chronic noncancer pain are common among drug counselors. Addressing these barriers in drug counselor training and in methadone maintenance treatment programs may benefit both methadone-maintained patients with chronic pain and their providers.